Making “inclusion” more than a buzzword: A critical interpretive synthesis of literature about recruiting seldom-heard groups in health research - Meghan Bradway; Lilisbeth Perestelo-Perez; Alezandra Torres-Castaño; Ana Maria Claudia Wagner; María Luisa Álvarez-Malé; Garlene Beatriz Zamora Zamorano; Kari Dyb (PLoS ONE, 2025)
Introduction Seldom-heard’ groups do not experience equitable access, engagement, or benefits from health services and are often underrepresented in research. Methods This paper presents a critical interpretive synthesis (CIS) of the literature. The included articles were those published between 2000 and 2024 in PubMed and Web of Science that focused on the recruitment and engagement of ‘seldom-heard’, ‘hard-to-reach’, or ‘disadvantaged’ groups in Europe. Purposive samples of articles followed a flexible and iterative review. Analysis and synthesis focused on identifying “synthetic constructs” or overarching themes, which informed the development of a “synthesizing argument” regarding recruitment and engagement strategies for seldom-heard groups. The presented paper focuses on the “synthetic constructs”, whereas the “synthetic argument” will be described in a subsequent paper. Results Of the 7601 articles identified, 23 were included. The analysis revealed four synthetic constructs: 1) the complexity of labels and identity, 2) the impact of labels on recruitment, 3) strategies to address recruitment challenges, and 4) the broader effects of these strategies on research and researchers. Conclusion Effective recruitment of seldom heard groups requires lengthy, careful planning, relationship-building, and an understanding of their unique perspectives. In doing so, researchers can contribute to reducing health inequalities and amplifying the voices of underrepresented populations.